A Comparative Study Of The Traditional Tendering And E-Tendering Methods In The Malaysian Context - Ramasamy, Gobi (2008)
This paper focuses on how the e-tendering system can replace the Traditional method, focusing on aspects such as Cost Saving, Time Factor and Efficiency fo rthe 3 major players; owners, consultants and contractors, Supplier and service providers.